Impact of dyslipidemia on cochleovestibular disorders in diabetic patients attending ENT Services at Boyambi Hospital, Kinshasa, Democratic Republic of the Congo - Linda, Henriette Mudwanga; Pholo Manzimbala , Jean Paul; Lema, Gabriel; Mafuta, Danny; Mfulani, Gibency; Matanda, Christian; Mbambu, Eddy; Matanda, Richard; Sokolo, Gedikondele Jérôme (Orapuh Journal, 2025)
Introduction Cochlear and vestibular disorders, particularly hearing loss, represent a public health concern in diabetic patients. Several factors may be responsible for this condition, including dyslipidemia (blood lipid imbalance).Purpose The aim of this study was to assess the impact of dyslipidemia on cochleovestibular disorders in diabetic patients attending ENT services at Boyambi Hospital, Kinshasa, Democratic Republic of the Congo.MethodsA cross-sectional study with analytical aims was conducted. All subjects underwent a thorough ENT examination to screen for cochleovestibular disorders and assess lipid levels. The collected data were analysed using SPSS 26.0 software.ResultsA total of 179 diabetic patients were included in this study, of whom 145 (81%) had type 2 diabetes mellitus and 34 (19%) had type 1 diabetes. Females were more represented (107; 59.8%). The mean patient age was 53±14 years. Hearing loss was the most common cochlear disorder (93.3%), while vertigo was the most prevalent vestibular disorder (20.7%). The Barany caloric test was abnormal in 12.8% of patients.ConclusionDiabetes mellitus characterised by a blood sugar level from 226 mg/dl and a glycated haemoglobin level greater than 7% is correlated with the occurrence of cochleovestibular disorders.